Justice and righteousness in Matthean Theology and its relevance to the Banyamulenge community: a post-colonial reading - Van Aarde, A.G. (Andries G.) (University of Pretoria, 2013)
Thesis (PhD (New Testament Studies))--University of Pretoria, 2007.